globalization, student, mental health, stress, adaptation, psychological support, education. (Universal International Scientific Journal, 2026)
The article analyzes the role of family psychology in the formation of moral and spiritual immunity, the influence of gender stereotypes and social consciousness in the upbringing of children. It examines the important role that psychological and social factors in the family environment play in the development of immunity against information attacks in children, as well as the influence of gender views and stereotypes on the formation of a child's social consciousness.
Keywords: Family psychology, moral and spiritual immunity, child rearing, gender stereotypes, social consciousness, information attacks.